Programmed cell death-like behavior in photoperiod-sensitive genic male sterile (PGMS) rice - Njiruh, Nthakanio P.; Qingzhong, Xue (Academic Journals, 2011)
In photoperiod-sensitive genic male sterile rice (Oryza sativa L.) pollen abort in long day and high temperature, and revert to fertility in short day length and low temperature growth conditions. This type of control of rice plant fertility can facilitate production of hybrid rice using two lines (photoperiodsensitive genic male sterile (PGMS) and restorer) system. Our objective in this study was to determine anatomical changes in PGMS rice pollen cells induced by long day length and high temperature growth conditions that are responsible for the cell abortion. All materials in this study were sown at Zhejiang University research field at Hangzhou, China 30°15’ N. Seeds of ZAU11S106, a PGMS rice line, were sown so as to obtain two bulks, 1) Extreme sterile pollen bulk and 2) fertile pollen bulk. Rice plants for extreme sterile pollen bulk were sown on March 18th and those for fertile pollen bulk on July 15th, so that they flowered under 13 h or more and under less than 13 h respectively of day light. Transmission electronic microscopes were used to study histological sections of anthers while light microscopes were used to examine whole pollen cells. The tapetal layers and the cytoplasm of the sectioned ZAU11S106 rice anthers from extreme sterile pollen bulk were deformed but those from fertile pollen bulk were normal when compared to the control rice lines ZAU11F121 and Xusui163. Pollen cells from anthers of extreme sterile pollen bulk had eroded exine and intine, missing or damaged nucleus, and disintegrating cytoplasm that lead to cell abortion. Our conclusion is that, cell abortion observed in extreme sterile pollen bulk of photoperiod genic male sterile rice, display “programmed cell death–like behavior”.
Keywords: Pollen cell abortion; photoperiod genic male sterile rice; programmed cell death-like; tapetum